The Effect Of Using Tiktok On Students’ Vocabulary Mastery In Seventh Grade At SMP Negeri 9 Pematang Siantar - Astrinia Ristama Tampubolon; Basar Lolo Siahaan; Anita Sitanggang (CV Putra Publisher, 2023)
The researcher decided to implement TikTok video in this research. The objective of this research is to find out the effect of using TikTok on students’ vocabulary mastery in seventh grade at SMP Negeri 9 Pematang Siantar academic year 2023/2024. This research used quasi-experimental design with quantitative method. In this research, the reseaarcher used two classes with the name experimental class and control class. The researcher took the population of seventh grade with the total number was 265 students. For the sample, in the experimental class and control class the number of students were same, there were 30. The sample for experimental class was VII-1 and the sample for control class was VII-2, students who were selected using purposive sampling technique. And to analyze the data, the researcher used the t-test formula to determine whether using TikTok had an effect on student’s vocabulary mastery. After analyze the data, the result of this research showed the mean score pre-test and post-test in the experimental class and the mean score of the pre-test and post-test in control class. While in the experimental class mean score pre-test was 60,5 and post-test was 80,3 And in the control class mean score pre-test was 60,16 and post-test was 70,66 For standard deviation in experimental class was 1.424,16 and standard deviation in control class was 867,5. After calculating the mean and standard deviation from both of class, the researcher calculating used t-test formula, the result was the t-test must highest from t-table with 5% level significance (5,761 > 1,697). Based on the finding of this research, the researcher conclude that the alternative hypothesis (Ha) is accepted and null hypothesis (H0) is rejected. So, it can be concluded that using TikTok has an effect on students’ vocabulary mastery especially in seventh grade.